BLE-Enabled Medication Events Monitoring System (MEMS) for community dwelling seniors - SUBRAMANIAM, Avinash (Institutional Knowledge at Singapore Management University, 2019)
In this paper, we propose a low-cost Medication Events Monitoring System (MEMS) that can be deployed as a stand-Alone solution for community dwelling seniors. The system comprises a mains-powered Raspberry Pi Zero W as the gateway, and a plastic box instrumented with a sensor node. The sensor node is composed of an Estimote beacon that is attached with a reed switch, and a magnet that is attached to the lid of the plastic box. We evaluate the performance of the MEMS in terms of its sensing accuracy and its transmission reliability through experiments conducted in a research laboratory environment. Our results suggest that the performance of the proposed MEMS depends on the event interval, as well as the distance between the MEMS node and the gateway. At 2m (8m) apart, reliable sensing and transmission can be achieved when the interval between box opening and closing events is 15 sec (20 sec) or greater. These conditions seem reasonable and will need to be further validated when deployed in a home setting for community dwelling seniors.